2005
DOI: 10.1080/13506280444000409
|View full text |Cite
|
Sign up to set email alerts
|

Time course of information processing during scene perception: The relationship between saccade amplitude and fixation duration

Abstract: 2005): Time course of information processing during scene perception: The relationship between saccade amplitude and fixation duration, Visual Cognition, 12:3, 473-494

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

64
379
10
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(457 citation statements)
references
References 43 publications
(62 reference statements)
64
379
10
4
Order By: Relevance
“…Likewise, in a preference rating task where participants had to choose which of ten paintings they preferred, Antes (1974) found that fixations during early viewing were shorter (È215 ms) than those during later viewing (È310 ms). Saccade amplitude has also been shown to change during viewing, with amplitudes decreasing as viewing time increases, and to stabilize during later viewing (Antes, 1974;Castelhano et al, 2009;Pannasch et al, 2008;Unema et al, 2005). Thus, there appears to be a tendency for short fixations and large saccades to characterize early viewing and for long fixations and small saccades to characterize later viewing.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, in a preference rating task where participants had to choose which of ten paintings they preferred, Antes (1974) found that fixations during early viewing were shorter (È215 ms) than those during later viewing (È310 ms). Saccade amplitude has also been shown to change during viewing, with amplitudes decreasing as viewing time increases, and to stabilize during later viewing (Antes, 1974;Castelhano et al, 2009;Pannasch et al, 2008;Unema et al, 2005). Thus, there appears to be a tendency for short fixations and large saccades to characterize early viewing and for long fixations and small saccades to characterize later viewing.…”
Section: Introductionmentioning
confidence: 99%
“…Although some have reported little to no change in fixations as viewing time increases (De Graef, Christiaens, & d'Ydewalle, 1990), several studies have noted a tendency for fixations to increase during initial viewing periods and to stabilize during later viewing (e.g., Antes, 1974;Friedman & Liebelt, 1981;Pannasch, Helmert, Roth, Herbold, & Walter, 2008;Unema, Pannasch, Joos, & Velichkovsky, 2005). Castelhano et al (2009), for example, analyzed the duration of the first five fixations following scene onset for their search and memory tasks and found for both tasks that fixation durations increased as viewing time increased and then remained stable during later viewing (after È2 s).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Small sac-55 cades would reflect a focal processing of the scene whereas large saccades would be used to get contextual information. The latter mechanism is associated to ambient processing (Follet et al, 2011;Unema et al, 2005). A second bias concerns the distribution of saccade orientations.…”
Section: Introductionmentioning
confidence: 99%